Using Self-Regulated Presentation to Minimize the Students’ Speaking Anxiety in Classroom Activities - Dhea Putri Herdiani; Eulis Rahmawati; Selnistia Hidayani (Journal of English Language Teaching and Cultural Studies, 2023)
This research investigates the use of self-regulated presentation to minimize the students’ speaking anxiety. This research was to find out whether teaching speaking by self-regulated presentation can increase students speaking anxiety. This research used a case study with (qualitative method). For taking a data, the researcher used an interview, questionnaire and observation. The participants of this research are the second year of Senior High School at SMA Nusantara Unggul Pekayon Tangerang Banten. This research takes 28 students. The research finding of the result showed that most of the students’ are at “Anxious” level. There are 13 students (46,4%) who experience “Anxious” level, 8 students (28,6 %) are in “very anxious” level, 7 students (25%) are in “Mildly Anxious”. This research also found that are four factors of students anxiety: Being rediculed and laughed, Students’ opinions about the Language Learning, Lack of Preparation and Teachers’ Personality. The last result of this research shows the using self-regulated presentation can minimize students’ speaking anxiety.